2018
DOI: 10.1016/j.scitotenv.2018.04.284
|View full text |Cite
|
Sign up to set email alerts
|

Combating hypoxia/anoxia at sediment-water interfaces: A preliminary study of oxygen nanobubble modified clay materials

Abstract: Combating hypoxia/anoxia is an increasingly common need for restoring natural waters suffering from eutrophication. Oxygen nanobubble modified natural particles were investigated for mitigating hypoxia/anoxia at the sediment-water interface (SWI) in a simulated column experiment. By adding oxygen nanobubble modified zeolites (ONMZ) and local soils (ONMS), the oxygen nanobubble concentrations (10-10 particles/mL) were several orders of magnitude higher in the water than the original water solution (10 particles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 49 publications
2
58
1
Order By: Relevance
“…Following the flocculation, a 1.5 cm thick capping was applied in the Lake Tai experiment (projects 3 and 4) using local soil. For the Cetian experiment (project 5), a 1 cm capping was applied using oxygen nanobubble-modified zeolite, which was prepared following the method described by [24]. Briefly, zeolite was placed in a pressure-resistant, airtight container to create a vacuum (−0.08 to −0.1MPa for 2 h), followed by oxygen nanobubble loading (0.12 to 0.15 MPa for 4 h), which was repeated three times to achieve super-saturation of O 2 in the zeolite micropores.…”
Section: Treatment and Sample Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Following the flocculation, a 1.5 cm thick capping was applied in the Lake Tai experiment (projects 3 and 4) using local soil. For the Cetian experiment (project 5), a 1 cm capping was applied using oxygen nanobubble-modified zeolite, which was prepared following the method described by [24]. Briefly, zeolite was placed in a pressure-resistant, airtight container to create a vacuum (−0.08 to −0.1MPa for 2 h), followed by oxygen nanobubble loading (0.12 to 0.15 MPa for 4 h), which was repeated three times to achieve super-saturation of O 2 in the zeolite micropores.…”
Section: Treatment and Sample Analysismentioning
confidence: 99%
“…These clays can stably hold the nanobubbles for months, so that once the oxygen is delivered by settling the clay particles onto the sediment, an aerobic capping layer is formed on top of the anaerobic sediment. This oxidized capping layer can prevent the consumption of dissolved oxygen in the water column by the anaerobic substances from the sediment underneath the capping layer [24,25]. Furthermore, it has been demonstrated that emissions of the greenhouse gases CH 4 and CO 2 from eutrophic waters can be substantially reduced through the oxygen nanobubble-MLS treatment [26].…”
Section: Introductionmentioning
confidence: 99%
“…Phosphorus and nitrogen have long been recognised as crucial nutrients for harmful algal growth in eutrophic waters [11]. In addition to the input of external pollutants from wastewater or runoff waters, the embedded sediment-bonded nutrients can be released back to the water column, especially under hypoxic conditions at sediment-water interfaces [12]. Thus, integrated restoration strategies always consider the control of both external and internal nutrient loadings.…”
Section: Overview Of the Special Issuementioning
confidence: 99%
“…The eutrophication of a river or lake has effects that can be perceived by the naked eye, such as the alteration of biota, turbid water, large amounts of aquatic plants, sediments and the development of organisms that prevent light from penetrating columns of water, which then leads to a decrease of dissolved oxygen [11][12][13].…”
Section: Introductionmentioning
confidence: 99%